Efektivitas Pelatihan Keajaiban Doa Islami Untuk Meningkatkan Kesejahteraan Emosi Pada Siswa SMK "X" Di Yogyakarta - Mumtaz Afridah; Hepi Wahyuningsih; Sumedi P Nugraha (JIP (Jurnal Intervensi Psikologi), 2018)
This experiment research aimed to examine the effect of Keajaiban Doa Islamic Training to improve emotional well-being of high school students in SMK “X” Yogyakarta. This research used non-randomized Pre and Posttest Control Group Design. Participants of this research were divided into two group, control and experiment groups. Keajaiban Doa Islamic Training was only gave to 14 respondents from experiment group and have identified as low emotional well-being score. They were asked to complete Simsek’s emotional well-being scale (Cronbach’s Alpha = 0,86) before and after experiment. The result showed significancy p=0.00 (p < 0.05) for the comparison level of g score on experiment and control respondents at pre and posttest.  It means that Keajaiban Doa Islamic Training could improved  emotional well-being  of  high  school students in SMK “X” Yogyakarta. Keywords: Emotional Well-Being,  Prayers,  Keajaiban  Doa  Islami, Training